Effect of inclusion of pentasulphate mixture and arsenic in diets given high level of selenium on feed intake and nutrient utilization in buffaloes - Kumar, Ajay; Datt, Chander; Prusty, Sonali; Kundu, S S; Mani, Veena (Indian Journal of Dairy Science, 2020)
Sixteen Murrah buffalo male calves were divided into 4 groups with 4 animals in each group, based on their body weight and age. The animals were fed on rations to supply 15% less of CP requirements as per NRC (2001). Â All the animals were fed a basal diet (0.41 ppm Se) comprising of paddy straw, concentrate mixture and green maize (Control, group T1). The animals in groups T2, T3 and T4 were also supplemented with 10 ppm of Se in the form of sodium selenite after 60 d of feeding. Thereafter, animals were given supplementary arsenic (40 ppm of diet) in form of sodium arsenite and pentasulphate mixture (9 g/100 kg BW) in groups T3 and T4, respectively in addition to Se (10 ppm) being already given. After 85 days of feeding, a metabolism trial was conducted in order to determine DM intake, nutrient digestibility and balances of N and Se. DM Intake was similar in all the groups. Digestibility of nutrients (DM, OM, EE, CF, NFE, NDF) and nitrogen retention was also not affected by dietary treatments to any significant extent, however, digestibility of CP and ADF was lower (P